Karakteristik Manuskrip Kuno Syekh Mudo Abdul Qadim Jorong Belubus Kabupaten Lima Puluh Kota - Salsabila Qatrunnada; Aufa Dzakiyyah Rahmi (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2024)
Historical evidence such as the ancient manuscripts that the author researched is not often found in this modern era. This is caused by a change in media carried out by legal or government officials so that the maintenance of these manuscripts is maintained and preserved. In this study, the author found one of the ancient manuscripts in Jorong Belubus, Limapuluh Kota Regency, where this manuscript already has several corruptions that have little chance of being used every day. This research aims to increase Islamic scientific knowledge and the existence of these ancient manuscripts can be further recorded and preserved so that they can be witnesses of Islamic civilization that occurred in that environment. This study focuses more on the characteristics of the manuscript as well as data related to the ancient manuscript, description of the manuscript, then analysis of the manuscript, why this manuscript exists, its purpose, why it is incomplete and the benefits of this book. This of course uses manuscript research methods (library research). The objectives or results of the manuscript research methodology can be the identity, condition and absence of the manuscript. The application and methodology of teirseibuit is the description of various physical aspects of a manuscript which include various characters or letters, various languages, and external characteristics of the manuscript. So several points can be produced in this research in the form of characteristics of mushafs that do not have colophon, have some corruption, use Usmani and Ilma'i rasm, but in this ancient manuscript it is more likely to use Imla'i rasm, and this manuscript will remain the main icon for the people. Naqsbandiyah order because Sheikh Mudo Abdul Qadim himself was a teacher as a great scholar, especially for the Naqsbandiyah order.